PROFITABILITY DAN FAKTOR LAINNYA YANG MEMPENGARUHI DEBT POLICY - Julieta, Villia; Viriany, Viriany (Jurnal Paradigma Akuntansi, 2025)
The main purpose of this research is analyze the effect of profitability, liquidity, asset structure and firm size on the debt policy, on consumer non-cyclical companies listed on Indonesian Stock Exchange in the period of 2018-2021. This research uses purposive sampling method, and there were 11 companies as samples for this research. The statistics method used was multiple regression analysis which are processed using EViews 12 Student Version software. Based on the results of this research, the variable profitability had no significant effect on debt policy. The variable liquidity and firm size had negative and significant effect on debt policy. While asset structure partially had a positive and significant effect on the debt policy.